The Influence Of Customer Rating, Distribution Reviews And Promotions On Fashion Purchase Decisions For Shopee Application Users - Haryanti, Eka; Susena, Karona Cahya; Hanila, Siti (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
The purpose of this research is to determine the influence of Customer Ratings, Distribution Reviews and Promotions on Fashion Purchase Decisions among Shopee Application Users. This research method is a quantitative method. The research results show that multiple linear regression Y = 21,967 + 0.141 X1 + 0.312 X2 + 0.129 X3 + 0.120. Where the coefficient is positive, meaning that there is a positive or unidirectional relationship between the customer rating (X1), distribution review (X2) promotion (X3) variables on fashion purchasing decisions (Y) among Shopee application users. The results of the customer twig test (XI) show a tcount of 2,350 > ttable 1.660 and significance 0.021 < 0.05, then the results of the Ha hypothesis are accepted and Ho is rejected, meaning that customer service has a positive and significant influence on fashion purchasing decisions among Shopee application users. The results of the distribution review test (X2) show tcount 5.086 > ttable 1.660 and significance 0.000 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that the distribution review has a positive and significant effect on fashion purchasing decisions for Shopee application users. Promotion test results (X3) show tcount 2.143 > ttable 1.660 and significance 0.035 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning promotion has a positive and significant effect on fashion purchasing decisions for Shopee application users. As a result of comparing the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 48,903 > 2.46, so it is concluded that accepting the hypothesis, meaning that there is a simultaneous influence between Customer Rating (XI), Distribution Review (X2), Promotion (X3) on Purchasing Decisions ( Y) Fashion for Shopee Application Users. This can be seen at the significance level of 0.000 <0.05.